White Blotches on Brown Skin: A Post-colonial Critique of "The Writing on My Forehead" - Dr. Zareena Qasim (University of Chitral Journal of Linguistics and Literature, 2023)
The formal colonial rule of Britain ended seven decades ago but the experience deeply influenced the minds of the masses and altered their lives and psyche for a long time to come. Post-colonial issues such as loss of identity, hybridity, otherness, appropriation etc are frequently highlighted by the Anglophone writers of sub-continent. The authors of Pakistani descent have contributed remarkably to post-colonial literature. The present research aims to analyse Nafisa Haji’s novel The Writing on My Forehead (2009) to investigate Western influence on the minds and behaviours of the people of the subcontinent. Homi K. Bhabha’s analytical lens (1994) is the primary guide for this research. Three elements of hybridity, namely mimicry, ambivalence, and unhomeliness, as proposed by Bhabha are explored. The concepts of diaspora and othering in the work under discussion are also briefly touched. This research is qualitative and descriptive in nature. The results of detailed textual analysis indicate that various characters are hybrids of East and West. The phenomena of ambivalence and mimicry can be clearly observed in their conduct and thinking. The most important characters in this regard are Saira, Adeeba (also known as Big Nanima) and Kasim who openly mimic the Western culture. Minor characters like Adeeba’s parents and Shabana, though averse to Western culture at the surface level, are unconsciously influenced by it. The phenomena of othering, diaspora and unhomeliness are also briefly touched. In this way, the present study sheds light on the impact of colonialism on the lives of colonial subjects and links it with the continued hegemony of West over the Easterners. It will be helpful for students, teachers and researchers who wish to study Haji’s fiction and the impact of the phenomenon of colonialism.